Assessment of Physical Carrying Capacity for Managing Sustainability at Religious Tourist Destinations - Ravinder Jangra; S.P. Kaushik (International Journal of Religious Tourism and Pilgrimage)
Increased interest in the sustainability of tourism development has initiated concerns about the capability of tourist destinations. This concept implies a threshold or a number of assumptions that are supported by destinations and due to uncontrolled tourism activity it is essential to regulate and manage visitors as well as destinations. In the recent past, many miss-haps have occurred at famous destinations because such large numbers of visitors are unsupported by the destinations. This study aims to provide a examination of visitor thresholds. It tries to estimate the carrying capacity of Braham Sarovar, a very famous Hindu religious destination in Kurukshetra, Haryana using methodology suggested by IUCN and IRC. Data were collected through field surveys of Pilgrims and beside that, a GIS approach is used to establish a framework for assessment of the study area. The study results that the destination provides a good carrying capacity and basic facilities are sufficient at this place for normal days but there needs to be additional facilities on certain specific occasions.ut there needs to be additional facilities on certain specific occasions.